PERANCANGAN SISTEM INFORMASI IMUNISASI POLIO PADA BALITA DI PUSKESMAS GAJAH MADA TEMBILAHAN - Mispah Mispah; Ilyas Ilyas (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2020)
The immunization is not a new thing in the world of health in Indonesia, but to this day, many parents who are still hesitant in deciding whether their child will be immunized. This is quite reasonable, due to lack of information and knowledge of parents about the benefits and importance of immunization for children. Some controversy is circulating about the immunization effect that makes children allergic, autism to seizures due to immunization. However, all the risks that can be avoided if parents know important information before immunization. Immunization now can be obtained anywhere, giving the immunization was done in place of health services, such as hospital, Maternity Clinic, Puskesmas, Posyandu, and private doctors’ clinic.